A Bibliometric Analysis of Internal Audit Research in Indonesia - Firdausi, Qonita; Safitri, Sari; Manulang, Novrianti; Dachlan, Fitriana; Santoso, Rachmat Agus (Manunggal Halim Jaya, 2025)
This research aims to describe the evolution of internal audit, focusing on identifying the most productive and cited articles, authors, countries, and institutions on this topic. The study used bibliometric analysis with VOSviewer software based on Scopus data, covering 490 articles published from 2017–2023. Data was collected using the